Communication with Older Adults: Challenges and Strategies in a Changing Context - Daylén Montenegro Lleó; Vivian Bárbara González Curbelo; Madeleidy Rodríguez Hidalgo (Revista Finlay)
Population aging is a global phenomenon that poses unique challenges. According to the World Health Organization, by 2050, it is estimated that one in six people worldwide will be over 60 years old. This demographic shift emphasizes the importance of studying how communication can empower older adults and fully integrate them into their communities. Achieving effective communication with older adults is essential for addressing their emotional needs, promoting their social integration, and maintaining their physical health. Therefore, the main challenges of communicating with older adults are analyzed, and interventions, based on recent research, are identified to foster meaningful interactions.